The Effect Of Motivation And Work Discipline On Employee Performance Pt. Adira Finance Bengkulu - Ramdona, Desti; Soleh, Ahmad; Fitriano, Yun (Journal of Business Management, 2025)
The success of a company is greatly influenced by the performance of its individual employees. Every company will always try to get the best performance from its employees, in the hope that the company's goals will be achieved. This study aims to determine the effect of motivation and work discipline on the performance of employees of PT Adira Finance Bengkulu City. Performance is the real behaviour that everyone displays as a work achievement produced by employees in accordance with their role (Rivai, 2019). Motivation is the drive or enthusiasm that arises within a person or employee to do something or work, motivation from outside both from superiors and the basis for fulfilling needs and a sense of satisfaction, as well as fulfilling responsibilities for the tasks assigned and carried out in the organisation (Robbins (2016). Indicators include: (physiological needs), (safety needs), (social needs), (esteem needs), (self-actualisation needs). Work discipline is the attitude or action of a person in obeying and being responsible for the rules and norms that have been listed in an entity or company (Rivai (2019). Indicators include: Attendance, Obedience, Adherence to work standards, High level of vigilance, Work ethically. This type of research is a type of quantitative descriptive research with a sample withdrawal method using total sampling technique. The number of respondents in this study were 66 people. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, respondent response analysis, multiple linear regression analysis, coefficient of determination, and also hypothesis testing. From the results of the multiple linear regression test, the regression equation is obtained as follows: Y = 53.481 + 0.930 (X1) + 0.539 (X2). The results of the t hypothesis test on the motivation variable tcount> ttable which is equal to (2.976> 1.66901) and sig value. (0.004 < α 0.05), the work discipline variable shows tcount> ttable (2.722> 1.66901) and sig value. (0,008 < α 0,05). The f test results show Fcount> Ftable 26.666> 2.75 and sig value. (0,000 < α 0,05). So it can be concluded that motivation and work discipline together have a positive and significant effect on the performance of employees of PT Adira Finance Bengkulu City.